A new species of the genus Nothobranchius (Cyprinodontiformes: Nothobranchiidae) from the coastal area of northeastern Mozambique - Valdesalici, Stefano (Zootaxa, 2007)
Specimens of a distinctive fish of the genus Nothobranchius were collected from an ephemeral pool, not directly linked to an adjacent river, from the coastal area of northeastern Mozambique. These specimens appear to be closely related to Nothobranchius melanospilus, known from eastern Tanzania and southeastern Kenya and to another as-yet undescribed species (Nothobranchius cf. melanospilus) from a geographically contiguous area of southern Tanzania and northern Mozambique. The new species (herein described as Nothobranchius hengstleri) is differentiated by several morphological characters, as well as by different male and female color patterns from the above-reported species and all the others members of the Nothobranchius melanospilus species group.